2010
DOI: 10.1111/j.1464-5491.2010.03109.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in pregnancy‐related outcomes in the offspring of diabetic mothers in Bavaria, Germany, during 1987–2007

Abstract: Although the risk of adverse pregnancy outcomes is still increased in diabetic mothers, considerable improvement has been achieved. We hypothesize that this improvement is possibly due to improved diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
3
23
0
2
Order By: Relevance
“…This is consistent with other studies that continue to show elevated perinatal mortality rates in women with pre-GDM captured past 2003 (13,14,32). Two studies that looked at the trend over time showed a nonsignificant decline in stillbirths/perinatal mortality (13,14).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with other studies that continue to show elevated perinatal mortality rates in women with pre-GDM captured past 2003 (13,14,32). Two studies that looked at the trend over time showed a nonsignificant decline in stillbirths/perinatal mortality (13,14).…”
Section: Discussionsupporting
confidence: 80%
“…There is little data on whether the rates of these serious outcomes have changed over time in women with diabetes. Only two studies have looked at trends in outcomes in women with diabetes over the last decade, in Germany (data up to 2004) and the U.K. (data up to 2007), and both failed to find significant decreases in perinatal mortality or congenital anomalies (13,14). Using unique population-based databases that link maternal and fetal health records, the aim of this population-based study was to compare rates of serious perinatal outcomes between women with and without diabetes in pregnancy, explore whether these rates have changed over time, and relate these rates to the underlying trends in rates of diabetes in pregnancy over the past 14 years.…”
mentioning
confidence: 99%
“…Numerous studies indicate that the rates of perinatal complications among type 1 diabetic patients are still substantially higher than those of the general population [4][5][6][7][8][9][10][11]. Only a few centres have shown improvement in the outcomes of type 1 diabetic pregnancies in recent decades [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Das zunehmende präkonzeptionelle Körpergewicht und Lebensalter der Frauen sind wichtige Trigger für die steigende Inzidenz der Erkrankung [1,2]. [4].…”
Section: Pathophysiologieunclassified